Intercalation Pseudocapacitance Boosting Ultrafast Sodium Storage in Prussian Blue Analogs. Issue 11 (17th May 2019) - Wang, Baoqi; Liu, Shuangyu; Sun, Wenping; Tang, Yuxin; Pan, Hongge; Yan, Mi; Jiang, Yinzhu
Abstract: Great expectation is placed on sodium‐ion batteries with high rate capability to satisfy multiple requirements in large‐scale energy storage systems. However, the large ionic radius and high mass of Na + hamper its kinetics in the case of diffusion‐controlled mechanisms in conventional electrodes. In this study, a unique intercalation pseudocapacitance has been demonstrated in low‐vacancy copper hexacyanoferrate, achieving outstanding rate capability. The minimization of the [Fe(CN)6 ] vacancy enables unhindered diffusion pathways for Na + and little structural change during the Fe 2+ /Fe 3+ redox reaction, eliminating solid‐state diffusion limits. Moreover, the Cu + /Cu 2+ couple is unexpectedly activated, realizing a record capacity for copper hexacyanoferrate. A capacity of 86 mAh g −1 is obtained at 1 C, of which 50 % is maintained under 100 C and 70 % is achieved at 0 °C. Such intercalation pseudocapacitance might shed light on exploiting high‐rate electrodes among Prussian blue analogs for advanced sodium‐ion batteries. Abstract : Into the blue : Intercalation pseudocapacitance is demonstrated in Prussian blue analogs for sodium storage of copper hexacyanoferrate. The minimization of the [Fe(CN)6 ] vacancy in copper hexacyanoferrate enables unhindered diffusion pathways for Na + and little structural change during the Fe 2+ /Fe 3+ redox reaction, eliminating solid‐state diffusion limits. High reversible capacity, outstanding rate capability, and long cycle life are achieved simultaneously.